TARI JAIPONG SEBAGAI INSPIRASI DESAIN INTERIOR HOTEL DI BANDUNG - Sherly Virthadani (Jurnal PATRA, 2021)
Globalization affects all aspects of people's lives, including changes in cultural values. This threatens the diversity and uniqueness of the existing local culture. In general, culture is more focused on universal form and uniformity. For this reason, efforts are needed to introduce and redevelop the cultural diversity of the local area. One of the strategies is to promote traditional culture as a source of inspiration in the interior design concept of a city hotel. This interior design uses the Jaipong Kawung Anten dance as a source of inspiration for City Hotel's interior design. The research method uses a qualitative method with a descriptive approach. Processing the design concept takes the character and philosophy of the Jaipong Kawung Anten dance. The Jaipong Kawung Anten dance tells the story of the daughter of Kawung Anten from the Sumedang Larang kingdom. The character of the dance is dynamic, varied, energetic, and masculine. The elements of the dance are implemented in the treatment of walls, floors, and the selection of furniture. Some elements of the Jaipong Kawung Anten dance are also processed into artwork and hotel interior ornaments. The choice of interior materials and colors also refers to the visualization of the Jaipong Kawung Anten dance. The results of this interior design are expected to become an iconic hotel in Bandung with the theme "Jaipong Kawung Anten". Through interior design, this can also be an effort to help preserve traditional Sundanese culture.